The effect of teaching prerequisite academic skills writing and reading on academic readiness prerequisite writing and reading skills of slow learner’s preschool children in Ahvaz - ehsan Kordi; Manijeh Shehni Yeilagh; Gholam Hossein Maktabi; askar Atash Afroz (مجله علوم روانشناختی)
Background: Learning disorders of slow learners have a negative effect on their education and skills related to education, such as writing, reading, math, etc. slow learner’s children have a different understanding of what they see and hear, and it is difficult for them to learn new information and skills. Despite the fact that these children constitute a large group of students, they have rarely been investigated in research. Aims: This research was conducted with the aim of determining the effect of teaching prerequisite academic skills on the prerequisite writing skills and prerequisite reading skills of slow learners. Methods: The current research design was semi-experimental, pre-test-post-test and 1-month follow-up with a control group. slow learner’s boys and girls in preschool centers in Ahvaz in the academic year of 2022-2023. Using multi-stage random sampling method, 40 eligible slow learners’ children were selected and randomly placed in two experimental and control groups. In this research, to collect data, a scale was used to determine the level of basic skills and educational prerequisites of slow learners in the preschool period (2016). Multivariate covariance analysis was used to analyze the research data. Results: The results of the research data showed that teaching prerequisite academic skills has a significant effect on the prerequisite writing skills and prerequisite reading skills of slow learner’s preschool children. Also, the findings showed that over time and after a one-month follow-up period, these effects remained at a significance level of p< 0.01. Conclusion: According to the findings, it is concluded that the prerequisite writing skills and prerequisite reading skills of slow learner’s preschoolers in the group that received training on prerequisite academic skills were significantly higher than the group that did not receive training on prerequisite academic skills. Therefore, it is necessary to put the education of pre-requisite academic skills on the agenda of preschool centers.